2022
DOI: 10.1177/18344909221119830
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related stressful experiences and posttraumatic stress disorder symptoms among college students in China: A moderated mediation model of perceived control over the future and empathy

Abstract: The current study aims to investigate the mediating effect of perceived control over the future and the moderating effect of empathy on the association between stressful experiences and PTSD symptoms among college students in China in response to COVID-19. A sample of 1,225 college students (70.69% were female, M age = 20.22 years, SD = 2.02) were recruited using web-based surveys at wave 1 (W1) and wave 2 (W2) longitudinally. Results showed that COVID-19-related stressful experiences were significantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 65 publications
(76 reference statements)
1
5
0
Order By: Relevance
“…Moreover, consistent with prior research (Hasking et al, 2021; Xiao et al, 2022; Yam et al, 2023; Ye et al, 2022), more exposure to pandemic-related stress experiences was associated with increases in problematic behaviors amid the pandemic, whereas receiving greater social support was linked to better behavioral adaptation to pandemic conditions (Rui & Guo, 2023). Specifically, family support (but not peer support) was protective for children and adolescents’ adaptation amid the pandemic, since having more family support was associated with fewer increases in self-injury behaviors during the pandemic.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, consistent with prior research (Hasking et al, 2021; Xiao et al, 2022; Yam et al, 2023; Ye et al, 2022), more exposure to pandemic-related stress experiences was associated with increases in problematic behaviors amid the pandemic, whereas receiving greater social support was linked to better behavioral adaptation to pandemic conditions (Rui & Guo, 2023). Specifically, family support (but not peer support) was protective for children and adolescents’ adaptation amid the pandemic, since having more family support was associated with fewer increases in self-injury behaviors during the pandemic.…”
Section: Discussionsupporting
confidence: 83%
“…Empirical research corroborates this finding, observing that individuals having prior exposure to adversities were at a higher risk of psychological distress (Fernández et al, 2020;Mazza et al, 2020) and non-suicidal self-injury behaviors (Plener, 2021;Yong et al, 2023) amid the pandemic. Moreover, stress experiences related to the pandemic may aggregate children and adolescents' maladaptation to pandemic situations (Ye et al, 2022). Prior research examining perceptions and experiences associated with the pandemic has observed a higher risk of problem behaviors among individuals who perceived greater pandemic-related stress, including more self-injury behaviors (Xiao et al, 2022) and greater smartphone addiction (Yam et al, 2023).…”
Section: Factors Associated With Behavioral Outcomes During the Covid...mentioning
confidence: 99%
“…Zhang et al (2022) showed that 41.9% of hospital pharmacists had mild to severe anxiety and depressive symptoms, and 29.4% had mild to severe anxiety and depressive symptoms. Ye et al (2022) found that COVID-19-related stressful experiences were significantly associated with PTSD symptoms, where perceived control over the future and empathy significantly moderated the relationship. Ying et al (2023) explored people's appreciation of three types of internet memes about the COVID-19 pandemic that conveyed feelings of humor, encouragement, and agreement.…”
Section: The Covid-19 Pandemic and Individual Mental Healthmentioning
confidence: 92%
“…The study by Kulesza et al (2022) used an online quasi-experimental and cohort approach. Four of the articles employed cross-sectional designs (Tan et al, 2023; Fernández et al, 2023; Yang et al, 2023; Zhang et al, 2022), while four other studies used a longitudinal design with 2-wave data (Chen et al, 2022; Wei et al, 2022; Ye et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation